Reprodução sexuada e a evolução de nichos tróficos em ácaros oribatídeos - Ribeiro, Renato Pereira (Ecologia, 2024)
Although most species of eukaryotic organisms reproduce sexually and their abundance is associated with greater genetic recombination, asexual reproduction may provide advantages in certain situations. Several studies suggest that the trophic niche can direct the selection of reproductive mode. However, they propose different predictions, about niche characteristics and resource abundance and diversity, which are not totally validated in nature. In this study, we tested the effect of the trophic niche on the reproductive mode of oribatid mites, numerically dominant soil detritivores in which around 10% of the estimated species consist of diploid clonal females. We gathered data on trophic niche (isotope ratios resulting from N and C) and reproductive mode of 148 populations of 94 species. We found that reproductive modes completely overlapped considering their trophic niche and had equivalent niche breadths after taking into account the effects of latitude and phylogeny. Therefore, we refute the idea that reproductive mode affects niche evolution and invalidate hypotheses based on this premise, such as the Tangled Bank Hypothesis and Structured Resource Theory.
Keywords: Amplitude de nicho; Partenogênese; Ácaros oribatídeos